A protocol for quantifying mono- and polysaccharides in seawater and related saline matrices by electro-dialysis (ED) – combined with HPAEC-PAD - Sebastian Zeppenfeld; Manuela van Pinxteren; Anja Engel; Hartmut Herrmann (Ocean Science, 2020)
An optimized method is presented to determine dissolved free (DFCHO) and dissolved combined carbohydrates (DCCHO) in saline matrices, such as oceanic seawater, Arctic ice core samples or brine using a combination of a desalination with electro-dialysis (ED) and high-performance anion exchange chromatography coupled to pulsed amperometric detection (HPAEC-PAD). Free neutral sugars, such as glucose and galactose, were found with 95 %–98 % recovery rates. Free amino sugars and free uronic acids were strongly depleted during ED at pH=8, but an adjustment of the pH could result in higher recoveries (58 %–59 % for amino sugars at pH=11; 45 %–49 % for uronic acids at pH=1.5). The applicability of this method for the analysis of DCCHO was evaluated with standard solutions and seawater samples compared with another established desalination method using membrane dialysis. DFCHO in field samples from different regions on Earth ranged between 11 and 118 nM and DCCHO between 260 and 1410 nM. This novel method has the potential to contribute to a better understanding of biogeochemical processes in the oceans and sea–air transfer processes of organic matter into the atmosphere in future studies.

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

Heterozygous HNRNPU variants cause early onset epilepsy and severe intellectual disability - Nuria C. Bramswig; Hermann-Josef Lüdecke; Fadi F. Hamdan; Janine Altmüller; Filippo Beleggia; Nursel H. Elcioglu; Catharine Freyer; Erica H. Gerkes; Yasemin Kendir Demirkol; Kelly G. Knupp; Alma Kuechler; Yun Li; et al. (Human Genetics, 2017)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Alma Kuechler; Marjolein H. Willemsen; Beate Albrecht; Carlos A. Bacino; Dennis W. Bartholomew; Hans van Bokhoven; Marie Jose H. van den Boogaard; Nuria Bramswig; Christian Büttner; Kirsten Cremer; Johanna Christina Czeschik; Hartmut Engels; et al. (Human Genetics, 2015)

Dissecting the genotype in syndromic intellectual disability using whole exome sequencing in addition to genome-wide copy number analysis - Carl Friedrich Classen; Vera Riehmer; Christina Landwehr; Anne Kosfeld; Stefanie Heilmann; Caroline Scholz; Sarah Kabisch; Hartmut Engels; Sascha Tierling; Miroslav Zivicnjak; Frank Schacherer; Dieter Haffner; et al. (Human Genetics, 2013)

The neurobeachin gene ( Nbea ) identifies a new region of homology between mouse central Chromosome 3 and human Chromosome 13q13 - Debra J. Gilbert; Hartmut Engel; Xiaolu Wang; Karl-Heinz Grzeschik; Neal G. Copeland; Nancy A. Jenkins; Manfred W. Kilimann (Mammalian Genome, 1999)

The structures of the human neuronal nicotinic acetylcholine receptor β2- and α3-subunit genes ( CHRNB2 and CHRNA3 ) - Nicole Rempel; Sibilla Heyers; Hartmut Engels; E. Sleegers; O. K. Steinlein (Human Genetics, 1998)

Molecular investigation of the parental origin of a de novo unbalanced translocation 13/18 - T. Eggermann; Hartmut Engels; Christiane Heidrich-Kaul; Inge Moderau; Gesa Schwanitz (Human Genetics, 1997)